Financial stability assessment of EU candidate and potential candidate countries: Developments since 2014 - Martin Gächter; Piotr Macki; Isabella Moder; Éva Katalin Polgár; Li Savelin; Piotr Żuk (European Central Bank (ECB), 2017)
This paper reviews and assesses financial stability challenges in countries preparing for EU membership, i.e. Albania, Bosnia and Herzegovina, Kosovo1, the former Yugoslav Republic of Macedonia, Montenegro, Serbia and Turkey. The paper focuses on the period since 2014 and on the banking sectors that dominate financial systems in this group of countries. It identifies two main near-term challenges applying to most of them. The first relates to credit risk, which remains substantial despite some progress in reducing the burden of non-performing loans on banks' balance sheets in the period under review. However, progress so far is limited, partly owing to structural impediments. The second relates to the still high share of foreign exchange denominated loans and deposits, which poses an indirect credit risk in the case of lending to unhedged borrowers and impairs the monetary transmission channel. In addition, profitability is worth monitoring going forward, as it remains subdued in many countries given high provisioning needs and a lacklustre credit growth and low interest rate environment. These concerns are generally met with a solid shock-absorbing capacity, as exemplified by robust capital and liquidity buffers.
Keywords: F31; F34; F36; G15; G21; G28; 330; Banking sector; financial stability; foreign exchange lending; credit growth; EU accession; Western Balkans; cross-border flows; deleveraging